A negative electrode composite material of an energy storage lead-carbon battery and a preparation method thereof
Patent Information
- Application Number
- CN202611116400.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-27
AI Technical Summary
碳材料偏析、陶瓷界面空隙、析氢与硫酸盐化功能割裂三重问题相互独立又相互关联,单一改进难以统筹解决,导致铅炭电池在HRPSoC工况下循环寿命不理想
[0029] 1. The conductive particles used in this application have lead powder as the core, and their overall density is close to that of lead powder. During the preparation of the negative electrode composite material for energy storage lead-carbon batteries, they can be uniformly dispersed, avoiding the segregation and floating caused by density differences in traditional carbon materials. The nitrogen-doped carbon layer on the surface of these conductive particles forms a continuous coating, allowing the lead powder particles to form a short-range conductive network through carbon shell contact. The bismuth nanoparticles anchored in the carbon layer interact with the nitrogen atoms in the nitrogen-doped carbon, increasing the hydrogen evolution overpotential on the carbon surface and suppressing hydrogen evolution side reactions caused by carbon materials.
Smart Images

Figure CN122638468B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a negative electrode composite material for energy storage lead-carbon batteries and its preparation method. Background Technology
[0002] Lead-carbon battery negative electrode composite materials, commonly known as negative electrode lead paste, are paste-like mixtures coated on the negative electrode grid. They are generally prepared by dry mixing, wet mixing, and acid addition followed by stirring, using components such as lead powder, carbon materials, expanding agents, fibers, and electrolytes. This composite material plays a dual role in lead-carbon batteries as both an electrochemical reactive material and a conductive network carrier; its composition and structure directly determine the battery's charge-discharge performance, cycle life, and safety. In energy storage applications, lead-carbon battery negative electrode composite materials need to adapt to high-rate partial state of charge (HRPSoC) conditions. Under these conditions, the battery frequently undergoes shallow charging and discharging, placing high demands on the negative electrode material's conductivity stability, resistance to sulfation, and hydrogen evolution inhibition capabilities.
[0003] Lead powder is the main component of the negative electrode composite material. During discharge, it reacts with sulfuric acid in the electrolyte to form lead sulfate, which is reduced back to lead during charging. To improve high-current charge-discharge performance and suppress sulfation, existing technologies typically add carbon materials such as activated carbon, carbon black, or graphene to the lead powder. These carbon materials have a much lower density than lead powder, and due to density differences, they are prone to floating and segregation during the wet mixing process of lead paste, resulting in uneven distribution of carbon materials in the electrode plates. Excessively high local carbon content can exacerbate the hydrogen evolution reaction, causing electrolyte water loss, while excessively low local carbon content prevents the formation of an effective conductive network, hindering electron transport during charge and discharge. Furthermore, the lack of chemical bonding between carbon materials and lead powder makes them prone to detaching from the lead matrix during cycling, leading to conductive network breakage and rapid performance degradation of the battery.
[0004] To construct a conductive framework and improve electrode porosity, some existing technologies introduce composites of porous ceramics and conductive carbon black. Porous ceramics themselves possess a stable framework structure, and the conductive carbon black filling the pores provides additional electron channels. However, the surface of porous ceramics is chemically inert and has poor wettability with lead paste, making it easy for interfacial voids to appear between ceramic particles and the lead matrix during formation. These voids gradually expand during cycling, leading to decreased electrode strength, accelerated shedding of active material, and ultimately capacity decay.
[0005] Regarding expanding agents, existing negative electrode composites typically incorporate a mixture of sodium lignosulfonate, humic acid, and barium sulfate. Barium sulfate, acting as a heterogeneous nucleation center for lead sulfate, ensures that the lead sulfate crystals generated during discharge are small and uniformly distributed, inhibiting the growth of large lead sulfate particles. Sodium lignosulfonate adsorbs onto the lead surface, preventing the formation of a dense passivation layer. Humic acid improves the plasticity of the lead paste through complexation. However, the functions of these expanding agent components are disconnected: sodium lignosulfonate primarily prevents passivation, humic acid primarily improves plasticity, and barium sulfate primarily inhibits sulfation; the three lack synergistic design. Hydrogen evolution inhibitors, such as bismuth oxide or gallium oxide, are usually added with the expanding agent through simple mechanical mixing. However, hydrogen evolution inhibitor particles tend to agglomerate and disperse unevenly, and they only address hydrogen evolution without directly contributing to sulfation inhibition. While carbon materials can inhibit sulfation, they can exacerbate hydrogen evolution; these functions are contradictory and difficult to achieve synergistic effects in a single composite material.
[0006] In summary, existing lead-carbon battery anode composite materials still have significant shortcomings in terms of carbon material dispersion uniformity, porous ceramic interface bonding, and the synergistic effect of hydrogen evolution suppression and sulfation suppression. The three problems of carbon material segregation, ceramic interface porosity, and the functional disconnect between hydrogen evolution and sulfation are independent yet interconnected, and cannot be comprehensively solved by a single improvement, resulting in unsatisfactory cycle life of lead-carbon batteries under HRPSoC conditions. Therefore, it is necessary to design a new anode composite material for energy storage lead-carbon batteries and its preparation method. Summary of the Invention
[0007] To overcome the shortcomings of existing technologies, a lead-carbon battery anode composite material for energy storage and its preparation method are provided.
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] A negative electrode composite material for energy storage lead-carbon batteries, comprising, by weight, 100 parts lead powder, 2-3.5 parts conductive particles, 1.5-2.5 parts conductive skeleton, 1.8-2.5 parts ternary composite expander, 0.1-0.15 parts short fibers, 9-11 parts dilute sulfuric acid, and 11-13 parts pure water.
[0010] The conductive particles are prepared by reacting lead powder in an alkaline buffer solution containing dopamine hydrochloride and bismuth nitrate pentahydrate and then pyrolyzing it.
[0011] The conductive framework was prepared by chemical vapor deposition and liquid-phase reduction deposition of porous alumina ceramic.
[0012] The ternary composite expanding agent is prepared by ball milling barium sulfate, sodium quaternized lignin sulfonate, and a bismuth-containing humic acid complex.
[0013] The method for preparing the conductive particles includes the following steps: dispersing lead powder in Tris-HCl buffer solution with a pH of 8.0-8.5, adding dopamine hydrochloride and bismuth nitrate pentahydrate, stirring openly at room temperature for 18-24 hours, filtering, washing with water, and vacuum drying at 60-80℃ to obtain lead powder coated with precursor.
[0014] Lead powder coated with precursor is pyrolyzed in a tube furnace, and after natural cooling, the product is ground for 10-15 minutes and passed through a 200-mesh sieve to obtain conductive particles.
[0015] The mass ratio of lead powder, dopamine hydrochloride, and bismuth nitrate pentahydrate is 100:3-5:0.8-1.5.
[0016] The specific steps and parameters of the pyrolysis are as follows: the lead powder coated with the precursor is placed in a tube furnace, and the temperature is increased to 280-300℃ at 2-3℃ / min under a nitrogen atmosphere, and held for 2-3 hours.
[0017] The method for preparing the conductive framework includes the following steps: placing spherical porous alumina ceramics with a particle size of 20 μm in a chemical vapor deposition furnace, using acetylene as the carbon source and nitrogen as the carrier gas, and performing chemical vapor deposition at 680-720℃ for 25-35 min to obtain a porous ceramic-conductive carbon black intermediate.
[0018] The porous ceramic-conductive carbon black intermediate was then immersed in an aqueous lead acetate solution and ultrasonically dispersed for 25-35 minutes. After that, hydrazine hydrate solution was added dropwise, and the mixture was stirred at room temperature for 2.5-3.5 hours to carry out liquid-phase reduction deposition. The mixture was then filtered and vacuum dried at 80-100℃ to obtain the conductive framework.
[0019] The concentration of the lead acetate aqueous solution is 0.08-0.12 mol / L, the mass percentage concentration of the hydrazine hydrate solution is 12%-18%, the amount of the lead acetate aqueous solution used is 20-40 mL per gram of porous ceramic-conductive carbon black intermediate, the amount of the hydrazine hydrate solution used is 50-100 mL per liter of lead acetate aqueous solution; the flow rate of the acetylene is 50-100 mL / min, and the flow rate of the nitrogen gas is 200-400 mL / min.
[0020] The preparation method of the ternary composite expanding agent includes the following steps:
[0021] Step 1: Preparation of sodium quaternized lignin sulfonate: Dissolve sodium lignin sulfonate in water to prepare a 15%-25% (w / w) solution. Adjust the pH to 9-10 with sodium hydroxide. Add 3-chloro-2-hydroxypropyltrimethylammonium chloride and react at 60-70℃ for 3-4 hours. Cool the reaction solution to room temperature and adjust the pH to 2-3 with dilute hydrochloric acid. After standing for 2-3 hours, filter the solution. Wash twice with dilute hydrochloric acid solution at pH 2-3, then wash once with deionized water, and finally wash twice with ethanol. Dry under vacuum at 60-70℃ to constant weight. Grind the solution and pass it through a 100-200 mesh sieve to obtain solid sodium quaternized lignin sulfonate.
[0022] Step 2: Preparation of bismuth-containing humic acid complex: Dissolve bismuth nitrate pentahydrate in 0.5-1 mol / L dilute nitric acid to prepare a bismuth nitrate pentahydrate solution with a concentration of 0.05-0.1 mol / L; dissolve humic acid in water to prepare a solution with a mass fraction of 8%-12%, and adjust the pH to 3-4 with dilute nitric acid to obtain a humic acid solution; add the humic acid solution to the bismuth nitrate pentahydrate solution dropwise over 0.5-1 h, maintaining a stirring speed of 200-300 r / min during the addition process, stirring at room temperature for 2-3 h, aging for 12 h, filtering, washing the filter cake with deionized water until the washing liquid is neutral, and vacuum drying at 60-70℃ to obtain the bismuth-containing humic acid complex;
[0023] The third step is to prepare a ternary composite expanding agent: barium sulfate, sodium quaternized lignin sulfonate, and bismuth-containing humic acid complex are ball-milled at a mass ratio of 5-6:1.5-2:1 to obtain the ternary composite expanding agent.
[0024] The mass ratio of humic acid to bismuth nitrate pentahydrate is 11-19:1; the mass ratio of sodium lignosulfonate to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:0.3-0.5.
[0025] The specific parameters for ball milling are as follows: barium sulfate, sodium quaternized lignin sulfonate, and bismuth-containing humic acid complex are placed in a ball mill, zirconium oxide balls are used as the grinding medium, the ball-to-material mass ratio is 6:1-8:1, the rotation speed is 300-350 r / min, and the ball milling time is 60-80 min.
[0026] The short fibers are polyester short fibers with a length of 2-4 mm and a diameter of 10-20 μm; the mass fraction of the dilute sulfuric acid is 40%.
[0027] A method for preparing a negative electrode composite material for energy storage lead-carbon batteries includes the following steps: dry mixing lead powder, conductive particles, conductive skeleton, ternary composite expander, and short fibers for 6-8 minutes; adding pure water and wet mixing for 4-5 minutes; adding dilute sulfuric acid while stirring for 10-12 minutes; continuing stirring for 16-20 minutes while maintaining a stirring speed of 150-250 r / min; and controlling the mixing temperature to not exceed 52℃ to obtain the negative electrode composite material for energy storage lead-carbon batteries.
[0028] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0029] 1. The conductive particles used in this application have lead powder as the core, and their overall density is close to that of lead powder. During the preparation of the negative electrode composite material for energy storage lead-carbon batteries, they can be uniformly dispersed, avoiding the segregation and floating caused by density differences in traditional carbon materials. The nitrogen-doped carbon layer on the surface of these conductive particles forms a continuous coating, allowing the lead powder particles to form a short-range conductive network through carbon shell contact. The bismuth nanoparticles anchored in the carbon layer interact with the nitrogen atoms in the nitrogen-doped carbon, increasing the hydrogen evolution overpotential on the carbon surface and suppressing hydrogen evolution side reactions caused by carbon materials.
[0030] 2. The conductive framework used in this application employs spherical porous alumina ceramic as the matrix. Conductive carbon black grown in situ within the pores provides abundant electron channels, forming a three-dimensional long-range conductive network in the negative electrode composite material of the energy storage lead-carbon battery. The metallic lead layer formed on the ceramic surface through liquid-phase reduction deposition improves the wettability and interfacial bonding between the ceramic and lead powder, preventing interfacial voids around the ceramic after formation. Conductive particles are embedded in the network nodes of the conductive framework, forming a point-network conductive structure. The conductive particles are responsible for short-range conduction between particles, while the conductive framework is responsible for long-range conduction within the electrode plate. Together, they reduce the internal resistance of the electrode plate and improve high-current charge-discharge performance.
[0031] 3. The ternary composite expanding agent used in this application is obtained by ball milling and premixing barium sulfate, sodium quaternized lignin sulfonate, and a bismuth-containing humic acid complex, and is uniformly dispersed in the negative electrode composite material of the energy storage lead-carbon battery. The quaternary ammonium groups introduced on the molecular chain of sodium quaternized lignin sulfonate enhance the electrostatic adsorption capacity with the lead surface and prevent lead surface passivation. During the formation process, the bismuth-containing humic acid complex is reduced to uniformly dispersed metallic bismuth particles, which are deposited on the surface of the negative electrode active material, increasing the hydrogen evolution overpotential and inhibiting hydrogen evolution. Barium sulfate, as a heterogeneous nucleation center for lead sulfate, makes the lead sulfate crystals generated during discharge small and uniformly distributed, limiting the growth space of large lead sulfate crystals. The three components complement each other, enabling the negative electrode to simultaneously possess a low hydrogen evolution rate and high resistance to sulfation under high-rate partial state of charge conditions.
[0032] 4. In the lead-carbon battery negative electrode composite material of this application, there is an indirect synergy between the conductive network and the interface protection system. The complete conductive network reduces the internal resistance of the electrode plate, makes the current distribution uniform, and reduces local overcharge and discharge, thereby mitigating local sulfation and local hydrogen evolution, and indirectly enhancing the protective effect of the expanding agent. Conversely, the ternary composite expanding agent prevents lead surface passivation and inhibits sulfation, maintaining the electrochemical activity of the lead powder surface, allowing the conductive network to continuously play its electron transport role. This synergy improves the negative electrode composite material in terms of conductivity, hydrogen evolution inhibition, and sulfation inhibition, thus extending the cycle life. Attached Figure Description
[0033] Figure 1 This is a process flow diagram of a method for preparing a negative electrode composite material for energy storage lead-carbon batteries. Detailed Implementation
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] In the specific embodiments of this application, the sources of various main raw materials are briefly described as follows:
[0036] Lead powder: purchased from Henan Yuguang Gold & Lead Co., Ltd., CAS No. 7439-92-1, particle size 1-3μm, purity ≥99.9%.
[0037] Dopamine hydrochloride: purchased from Hubei Hengjie Chemical Co., Ltd., CAS No. 62-31-7, purity ≥98%.
[0038] Bismuth nitrate pentahydrate: purchased from Wuhan Jiyesheng Chemical Co., Ltd., CAS No. 10035-06-0, purity ≥98%.
[0039] Tris-HCl buffer: purchased from Shanghai Lianmai Biotechnology Co., Ltd., pH 8.0.
[0040] Spherical porous alumina ceramics: purchased from Jiangxi Hengerwo Chemical Co., Ltd., CAS No. 1344-28-1, particle size 20μm, porosity ≥60%, α phase.
[0041] Lead acetate: purchased from Wuhan Kanos Technology Co., Ltd., CAS No. 6080-56-4, purity ≥99%, is lead acetate trihydrate.
[0042] Hydrazine hydrate: purchased from Jinan Boxin Chemical Co., Ltd., CAS No. 7803-57-8, mass fraction 80%, colorless and transparent liquid.
[0043] 3-Chloro-2-hydroxypropyltrimethylammonium chloride: purchased from Shandong Yukang Chemical Co., Ltd., CAS No. 3327-22-8, colorless to pale yellow liquid.
[0044] Humic acid: Purchased from Inner Mongolia Yongye Humic Acid Co., Ltd., CAS No. 1415-93-6, humic acid content ≥60%, raw powder.
[0045] Barium sulfate: purchased from Guizhou Hongtai Barium Industry Co., Ltd., CAS No. 7727-43-7, purity ≥98%, white powder.
[0046] Zirconia balls: purchased from Pingxiang Keyuan Environmental Protection Equipment Packing Co., Ltd., CAS No. 1314-23-4, particle size 10mm.
[0047] Polyester staple fiber: Purchased from Yangzhou Tianlun Fiber Co., Ltd., cut to length of 2-4mm, diameter of 10-20μm, fineness of 1.5-3D, and made to order. These are battery-specific short-cut polyester fibers.
[0048] Sulfuric acid: purchased from Guangdong Daxiao Chemical Co., Ltd., CAS No. 7664-93-9, prepared as 40% by mass dilute sulfuric acid with a density of approximately 1.30 g / cm3.
[0049] Sodium lignosulfonate: purchased from Wuhan Jiyesheng Chemical Co., Ltd., CAS No. 8061-51-6.
[0050] The technical solution of this application is as follows:
[0051] A negative electrode composite material for energy storage lead-carbon batteries, comprising, by weight, 100 parts lead powder, 2-3.5 parts conductive particles, 1.5-2.5 parts conductive skeleton, 1.8-2.5 parts ternary composite expander, 0.1-0.15 parts short fibers, 9-11 parts dilute sulfuric acid, and 11-13 parts pure water.
[0052] The conductive particles are prepared by reacting lead powder in an alkaline buffer solution containing dopamine hydrochloride and bismuth nitrate pentahydrate and then pyrolyzing it.
[0053] The conductive framework was prepared by chemical vapor deposition and liquid-phase reduction deposition of porous alumina ceramic.
[0054] The ternary composite expanding agent is prepared by ball milling barium sulfate, sodium quaternized lignin sulfonate, and a bismuth-containing humic acid complex.
[0055] The method for preparing the conductive particles includes the following steps: dispersing lead powder in Tris-HCl buffer solution with a pH of 8.0-8.5, adding dopamine hydrochloride and bismuth nitrate pentahydrate, stirring openly at room temperature for 18-24 hours, filtering, washing with water, and vacuum drying at 60-80℃ to obtain lead powder coated with precursor.
[0056] Lead powder coated with precursor is pyrolyzed in a tube furnace, and after natural cooling, the product is ground for 10-15 minutes and passed through a 200-mesh sieve to obtain conductive particles.
[0057] The mass ratio of lead powder, dopamine hydrochloride, and bismuth nitrate pentahydrate is 100:3-5:0.8-1.5.
[0058] The specific steps and parameters of the pyrolysis are as follows: the lead powder coated with the precursor is placed in a tube furnace, and the temperature is increased to 280-300℃ at 2-3℃ / min under a nitrogen atmosphere, and held for 2-3 hours.
[0059] In the research of anode composite materials for lead-carbon batteries, the segregation caused by the density difference between carbon materials and lead powder has been a long-standing problem. Traditional carbon materials have a much lower density than lead powder, making them prone to segregation during wet mixing and lacking chemical bonding with lead powder, leading to easy detachment during cycling. This application uses conductive particles to solve these problems. These conductive particles use lead powder as a core, with a core density close to that of the main lead powder, allowing for uniform dispersion in lead paste and avoiding segregation caused by density differences. A bismuth-containing precursor layer is formed on the lead powder surface through polydopamine self-polymerization. After pyrolysis, the polydopamine is converted into a nitrogen-doped carbon layer, while the coated bismuth species are simultaneously reduced in situ by carbothermal reduction to metallic bismuth nanoparticles and anchored within the carbon layer. The nitrogen-doped carbon layer forms a continuous conductive coating on the lead powder surface, creating a short-range conductive network between lead powder particles through carbon shell contacts. The nitrogen atoms in the carbon layer alter the electronic structure of the carbon surface, increasing the hydrogen evolution overpotential. Bismuth nanoparticles anchored in the carbon layer further enhance the hydrogen evolution overpotential on the carbon surface because bismuth itself has a high hydrogen evolution overpotential. Together with nitrogen-doped carbon, they suppress the hydrogen evolution side reaction caused by carbon materials.
[0060] The method for preparing the conductive framework includes the following steps: placing spherical porous alumina ceramics with a particle size of 20 μm in a chemical vapor deposition furnace, using acetylene as the carbon source and nitrogen as the carrier gas, and performing chemical vapor deposition at 680-720℃ for 25-35 min to obtain a porous ceramic-conductive carbon black intermediate.
[0061] The porous ceramic-conductive carbon black intermediate was then immersed in an aqueous lead acetate solution and ultrasonically dispersed for 25-35 minutes. After that, hydrazine hydrate solution was added dropwise, and the mixture was stirred at room temperature for 2.5-3.5 hours to carry out liquid-phase reduction deposition. The mixture was then filtered and vacuum dried at 80-100℃ to obtain the conductive framework.
[0062] The concentration of the lead acetate aqueous solution is 0.08-0.12 mol / L, the mass percentage concentration of the hydrazine hydrate solution is 12%-18%, the amount of the lead acetate aqueous solution used is 20-40 mL per gram of porous ceramic-conductive carbon black intermediate, the amount of the hydrazine hydrate solution used is 50-100 mL per liter of lead acetate aqueous solution; the flow rate of the acetylene is 50-100 mL / min, and the flow rate of the nitrogen gas is 200-400 mL / min.
[0063] The composite of porous ceramics and conductive carbon black has advantages in constructing a three-dimensional conductive framework. However, the ceramic surface is chemically inert, has poor wettability with lead paste, and is prone to interfacial voids after formation, leading to a decrease in electrode strength. This application uses a conductive framework to solve the above problems. The conductive framework uses spherical porous alumina ceramic as the matrix. Acetylene is pyrolyzed within the ceramic channels through chemical vapor deposition, resulting in the in-situ growth of conductive carbon black, forming a porous ceramic-conductive carbon black intermediate. This intermediate is then immersed in an aqueous solution of lead acetate, and hydrazine hydrate is added dropwise for liquid-phase reduction deposition. The hydrazine hydrate reduces the lead acetate to metallic lead, which is deposited on the ceramic surface to form a metallic lead layer. The conductive carbon black grown in situ within the channels provides abundant electron channels, forming a three-dimensional long-range conductive network in the lead paste. The metallic lead layer deposited on the ceramic surface improves the wettability and interfacial bonding between the ceramic and lead powder, because the lead layer gives the ceramic surface similar metallic properties to the lead powder, avoiding interfacial voids around the ceramic after formation. Conductive particles are embedded in the network nodes of the conductive framework to form a point-network conductive structure. The conductive particles are responsible for short-range conduction between particles, while the conductive framework is responsible for long-range conduction within the electrode. Together, they reduce the internal resistance of the electrode and improve the high-current charge and discharge performance.
[0064] The preparation method of the ternary composite expanding agent includes the following steps:
[0065] Step 1: Preparation of sodium quaternized lignin sulfonate: Dissolve sodium lignin sulfonate in water to prepare a 15%-25% (w / w) solution. Adjust the pH to 9-10 with sodium hydroxide. Add 3-chloro-2-hydroxypropyltrimethylammonium chloride and react at 60-70℃ for 3-4 hours. Cool the reaction solution to room temperature and adjust the pH to 2-3 with dilute hydrochloric acid. After standing for 2-3 hours, filter the solution. Wash twice with dilute hydrochloric acid solution at pH 2-3, then wash once with deionized water, and finally wash twice with ethanol. Dry under vacuum at 60-70℃ to constant weight. Grind the solution and pass it through a 100-200 mesh sieve to obtain solid sodium quaternized lignin sulfonate.
[0066] Step 2: Preparation of bismuth-containing humic acid complex: Dissolve bismuth nitrate pentahydrate in 0.5-1 mol / L dilute nitric acid to prepare a bismuth nitrate pentahydrate solution with a concentration of 0.05-0.1 mol / L; dissolve humic acid in water to prepare a solution with a mass fraction of 8%-12%, and adjust the pH to 3-4 with dilute nitric acid to obtain a humic acid solution; add the humic acid solution to the bismuth nitrate pentahydrate solution dropwise over 0.5-1 h, maintaining a stirring speed of 200-300 r / min during the addition process, stirring at room temperature for 2-3 h, aging for 12 h, filtering, washing the filter cake with deionized water until the washing liquid is neutral, and vacuum drying at 60-70℃ to obtain the bismuth-containing humic acid complex;
[0067] The third step is to prepare a ternary composite expanding agent: barium sulfate, sodium quaternized lignin sulfonate, and bismuth-containing humic acid complex are ball-milled at a mass ratio of 5-6:1.5-2:1 to obtain the ternary composite expanding agent.
[0068] The mass ratio of humic acid to bismuth nitrate pentahydrate is 11-19:1; the mass ratio of sodium lignosulfonate to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:0.3-0.5.
[0069] The specific parameters for ball milling are as follows: barium sulfate, sodium quaternized lignin sulfonate, and bismuth-containing humic acid complex are placed in a ball mill, zirconium oxide balls are used as the grinding medium, the ball-to-material mass ratio is 6:1-8:1, the rotation speed is 300-350 r / min, and the ball milling time is 60-80 min.
[0070] In existing expanding agents, the functions of sodium lignin sulfonate, humic acid, and barium sulfate are fragmented, and the hydrogen evolution inhibitor and sulfation inhibitor are difficult to coordinate. This application uses a ternary composite expanding agent to solve the above problems. This ternary composite expanding agent is obtained by ball milling and premixing barium sulfate, quaternized sodium lignin sulfonate, and a bismuth-containing humic acid complex. In the preparation of quaternized sodium lignin sulfonate, the phenolic hydroxyl group in the sodium lignin sulfonate molecule undergoes an etherification reaction with 3-chloro-2-hydroxypropyltrimethylammonium chloride, introducing a quaternary ammonium group onto the molecular chain. The quaternary ammonium group carries a positive charge and generates electrostatic adsorption with the negatively charged lead sulfate layer or lead oxide layer on the lead surface. The adsorption strength is higher than that of unmodified sodium lignin sulfonate, resulting in a more durable effect in preventing lead surface passivation. In the preparation of the bismuth-containing humic acid complex, the carboxyl group and phenolic hydroxyl group in the humic acid molecule undergo a coordination reaction with bismuth, fixing bismuth onto the humic acid molecular backbone. In the bismuth-containing humic acid complex, bismuth coordinates with the carboxyl groups of humic acid. This bismuth-containing humic acid complex is uniformly dispersed in lead paste. During formation, the bismuth in the complex is reduced to metallic bismuth nanoparticles, which deposit on the surface of the negative electrode active material. This increases the hydrogen evolution overpotential and continuously suppresses hydrogen evolution, avoiding the problems of uneven bismuth distribution and excessively rapid initial release when directly adding bismuth oxide. Barium sulfate, as a heterogeneous nucleation center for lead sulfate, ensures that the generated lead sulfate crystals are small and uniformly distributed, limiting the growth space of large lead sulfate crystals. After ball milling and premixing, the dispersibility of these three components is improved, resulting in uniform distribution in the lead paste. Their complementary functions enable the negative electrode to simultaneously exhibit a low hydrogen evolution rate and high resistance to sulfation under high-rate partial charge conditions.
[0071] The short fibers are polyester short fibers with a length of 2-4 mm and a diameter of 10-20 μm; the mass fraction of the dilute sulfuric acid is 40%.
[0072] A method for preparing a negative electrode composite material for energy storage lead-carbon batteries, such as... Figure 1 As shown, the method includes the following steps: dry mixing lead powder, conductive particles, conductive skeleton, ternary composite expansion agent, and short fibers for 6-8 minutes; adding pure water and wet mixing for 4-5 minutes; adding dilute sulfuric acid while stirring for 10-12 minutes; continuing stirring for 16-20 minutes while maintaining a stirring speed of 150-250 r / min; and controlling the mixing temperature to not exceed 52℃ to obtain the negative electrode composite material for energy storage lead-carbon batteries.
[0073] After the conductive particles, conductive framework, and ternary composite expander have each addressed their respective issues, there is also an indirect synergy among them. A complete conductive network reduces the internal resistance of the electrode plates, resulting in more uniform current distribution and reduced local overcharge and discharge, thereby mitigating local sulfation and hydrogen evolution, and indirectly enhancing the protective effect of the expander. Conversely, the ternary composite expander prevents lead surface passivation and inhibits sulfation, maintaining the electrochemical activity of the lead powder surface, enabling the conductive network to continuously perform electron transport functions and extending cycle life.
[0074] The present invention will be described in detail below through examples and comparative examples, but the scope of protection of the present invention is not limited to these examples. Unless otherwise specified, the chemical reagents and raw materials used in the following examples and comparative examples are all conventional commercially available products.
[0075] Example 1
[0076] Lead powder with a particle size of 2 μm was dispersed in Tris-HCl buffer solution with a pH of 8.0. Dopamine hydrochloride and bismuth nitrate pentahydrate were added in a mass ratio of lead powder, dopamine hydrochloride, and bismuth nitrate pentahydrate of 100:5:1.15. The mixture was stirred openly at room temperature for 18 h, filtered, washed with water, and vacuum dried at 60 °C to obtain precursor-coated lead powder. The precursor-coated lead powder was placed in a tube furnace and heated to 280 °C at a rate of 2.5 °C / min under a nitrogen atmosphere, held at this temperature for 3 h, and after natural cooling, the product was ground for 10 min and passed through a 200-mesh sieve to obtain conductive particles.
[0077] Spherical porous alumina ceramics with a particle size of 20 μm were placed in a chemical vapor deposition furnace. Acetylene was used as the carbon source and nitrogen as the carrier gas. The acetylene flow rate was 50 mL / min and the nitrogen flow rate was 300 mL / min. Chemical vapor deposition was carried out at 720 °C for 30 min to obtain a porous ceramic-conductive carbon black intermediate. The porous ceramic-conductive carbon black intermediate was then immersed in a 0.10 mol / L lead acetate aqueous solution at a concentration of 40 mL per gram of the porous ceramic-conductive carbon black intermediate. After ultrasonic dispersion for 25 min, a 15% (w / w) hydrazine hydrate solution was added dropwise at a concentration of 100 mL per liter of lead acetate aqueous solution. The mixture was stirred at room temperature for 2.5 h for liquid-phase reduction deposition. After filtration and vacuum drying at 80 °C, a conductive framework was obtained.
[0078] The first step involves dissolving sodium lignin sulfonate in water to prepare a 20% (w / w) solution. The pH is adjusted to 9 with sodium hydroxide. Then, 3-chloro-2-hydroxypropyltrimethylammonium chloride is added, with a mass ratio of sodium lignin sulfonate to 3-chloro-2-hydroxypropyltrimethylammonium chloride of 1:0.3. The reaction is carried out at 60°C for 4 hours. The reaction solution is then cooled to room temperature, and the pH is adjusted to 2 with dilute hydrochloric acid. After standing for 3 hours, the solution is filtered, washed twice with dilute hydrochloric acid solution at pH 2, washed once with deionized water, and finally washed twice with ethanol. The solution is then vacuum dried at 60°C to constant weight, ground, and passed through a 100-mesh sieve to obtain solid quaternized sodium lignin sulfonate. The second step involves dissolving bismuth nitrate pentahydrate in 0.5 mol / L dilute nitric acid to prepare a 0.1 mol / L bismuth nitrate pentahydrate solution. Humic acid is dissolved in water to prepare a 10% (w / w) solution. The pH is adjusted to 3 with dilute nitric acid to obtain a humic acid solution. This humic acid solution is then added dropwise to the bismuth nitrate pentahydrate solution over 0.5 hours, maintaining a stirring speed of 250 rpm during the addition process. Stirring is continued at room temperature for 3 hours, followed by aging for 12 hours. The filter cake is then washed with deionized water until the washing liquid is neutral, and vacuum dried at 60°C to obtain a bismuth-containing humic acid complex. The third step involves placing barium sulfate, sodium quaternized lignin sulfonate, and the bismuth-containing humic acid complex in a ball mill at a mass ratio of 6:2:1. Zirconia balls are used as the grinding medium, with a ball-to-material mass ratio of 6:1, and the milling speed is 300 rpm for 80 minutes to obtain a ternary composite expanding agent.
[0079] 100 parts of lead powder, 2.75 parts of conductive particles, 1.5 parts of conductive skeleton, 2.5 parts of ternary composite expander, and 0.1 parts of short fiber were dry-mixed for 8 minutes. Then, 13 parts of pure water were added and wet-mixed for 4 minutes. Under stirring, 11 parts of 40% dilute sulfuric acid were added for 10 minutes. Stirring was continued for 16 minutes at a stirring speed of 200 r / min, and the mixing temperature was controlled not to exceed 52℃ to obtain the negative electrode composite material for energy storage lead-carbon batteries.
[0080] Example 2
[0081] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0082] In the preparation of conductive particles, the mass ratio of lead powder, dopamine hydrochloride, and bismuth nitrate pentahydrate was 100:3:1.5. The mixture was stirred openly at room temperature for 24 hours, then filtered, washed with water, and vacuum dried at 80℃. The lead powder coated with the precursor was placed in a tube furnace and heated to 300℃ at a rate of 2.5℃ / min under a nitrogen atmosphere, held at that temperature for 2 hours, and after natural cooling, the product was ground for 15 minutes and passed through a 200-mesh sieve to obtain conductive particles.
[0083] In the preparation of the conductive framework, acetylene flow rate was 100 mL / min, nitrogen flow rate was 300 mL / min, and chemical vapor deposition was performed at 680℃ for 35 min to obtain a porous ceramic-conductive carbon black intermediate. The amount of lead acetate aqueous solution was 20 mL per gram of porous ceramic-conductive carbon black intermediate, and the amount of hydrazine hydrate solution was 50 mL per liter of lead acetate aqueous solution. Liquid phase reduction deposition was performed by stirring at room temperature for 3.5 h, followed by filtration and vacuum drying at 100℃ to obtain the conductive framework.
[0084] In the preparation of the ternary composite expansion agent, the sodium lignosulfonate solution had a mass fraction of 25%, the reaction temperature was 70℃, the reaction time was 3h, the bismuth nitrate pentahydrate solution concentration was 0.05mol / L, the humic acid solution had a mass fraction of 10%, the dropping time was 1h, and the ball milling time was 60min.
[0085] In the preparation of the composite material, 2 parts of conductive particles, 2.5 parts of conductive skeleton, 1.8 parts of ternary composite expansion agent, and 0.15 parts of short fiber were mixed with 11 parts of pure water for 5 minutes. Then, 9 parts of 40% dilute sulfuric acid were added for 12 minutes. The mixture was stirred for another 20 minutes at a stirring speed of 150 r / min.
[0086] Example 3
[0087] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0088] In the preparation of conductive particles, the mass ratio of lead powder, dopamine hydrochloride, and bismuth nitrate pentahydrate was 100:4:0.8. The mixture was stirred openly at room temperature for 21 hours, filtered, washed with water, and dried under vacuum at 70°C. The lead powder coated with the precursor was placed in a tube furnace and heated to 290°C at a rate of 2.5°C / min under a nitrogen atmosphere, held at that temperature for 2.5 hours, and after natural cooling, the product was ground for 12 minutes and passed through a 200-mesh sieve to obtain conductive particles.
[0089] In the preparation of the conductive framework, acetylene flow rate was 75 mL / min, nitrogen flow rate was 300 mL / min, and chemical vapor deposition was performed at 700℃ for 25 min to obtain a porous ceramic-conductive carbon black intermediate. The amount of lead acetate aqueous solution was 30 mL per gram of porous ceramic-conductive carbon black intermediate, and the amount of hydrazine hydrate solution was 75 mL per liter of lead acetate aqueous solution. Liquid phase reduction deposition was performed by stirring at room temperature for 3 h, followed by filtration and vacuum drying at 90℃ to obtain the conductive framework.
[0090] In the preparation of the ternary composite expanding agent, the sodium lignosulfonate solution had a mass fraction of 15%, the reaction temperature was 65℃, the reaction time was 3.5h, the bismuth nitrate pentahydrate solution concentration was 0.075mol / L, the humic acid solution had a mass fraction of 8%, the dropping time was 0.75h, and the ball milling time was 70min.
[0091] In the preparation of the composite material, 3.5 parts of conductive particles, 2 parts of conductive skeleton, 2.15 parts of ternary composite expansion agent, and 0.12 parts of short fiber were mixed with 12 parts of pure water for 4.5 min, 10 parts of 40% dilute sulfuric acid were added for 11 min, and stirring was continued for 18 min at a stirring speed of 250 r / min.
[0092] Example 4
[0093] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0094] In the preparation of conductive particles, the mass ratio of lead powder, dopamine hydrochloride, and bismuth nitrate pentahydrate was 100:4:1.2. The mixture was stirred in an open container at room temperature for 21 hours, then filtered, washed with water, and vacuum dried at 70°C. The lead powder coated with the precursor was placed in a tube furnace and heated to 290°C at a rate of 2.5°C / min under a nitrogen atmosphere, held at that temperature for 2.5 hours, and after natural cooling, the product was ground for 12 minutes and passed through a 200-mesh sieve to obtain conductive particles.
[0095] In the preparation of the conductive framework, acetylene flow rate was 80 mL / min, nitrogen flow rate was 300 mL / min, and chemical vapor deposition was performed at 700℃ for 30 min to obtain a porous ceramic-conductive carbon black intermediate. The amount of lead acetate aqueous solution was 30 mL per gram of porous ceramic-conductive carbon black intermediate, and the amount of hydrazine hydrate solution was 75 mL per liter of lead acetate aqueous solution. Liquid phase reduction deposition was performed by stirring at room temperature for 3 h, followed by filtration and vacuum drying at 90℃ to obtain the conductive framework.
[0096] In the preparation of the ternary composite expanding agent, the sodium lignosulfonate solution had a mass fraction of 20%, the reaction temperature was 65℃, the reaction time was 3.5h, the bismuth nitrate pentahydrate solution concentration was 0.08mol / L, the humic acid solution had a mass fraction of 10%, the dropping time was 0.75h, and the ball milling time was 70min.
[0097] In the preparation of the composite material, 3 parts of conductive particles, 2 parts of conductive skeleton, 2.2 parts of ternary composite expansion agent, and 0.12 parts of short fiber were mixed with 12 parts of pure water for 4.5 min, 10 parts of 40% dilute sulfuric acid were added for 11 min, and stirring was continued for 18 min at a stirring speed of 200 r / min.
[0098] Comparative Example 1
[0099] In this comparative example, the similarities with Example 4 will not be repeated, and the differences are as follows:
[0100] In the preparation of conductive particles, bismuth pentahydrate was not added, the mass ratio of lead powder to dopamine hydrochloride was 100:4, and the remaining steps and parameters were the same as those in the preparation of conductive particles in Example 4, resulting in nitrogen-doped carbon-coated lead conductive particles without bismuth anchoring.
[0101] Comparative Example 2
[0102] In this comparative example, the similarities with Example 4 will not be repeated, and the differences are as follows:
[0103] The liquid-phase reduction deposition step is omitted in the preparation of the conductive framework. That is, the porous ceramic-conductive carbon black intermediate is used directly as the conductive framework without immersion in lead acetate aqueous solution and addition of hydrazine hydrate solution.
[0104] Comparative Example 3
[0105] In this comparative example, the similarities with Example 4 will not be repeated, and the differences are as follows:
[0106] In the second step of preparing the ternary composite expanding agent, bismuth nitrate pentahydrate is not used. Instead, humic acid and bismuth oxide are simply mechanically mixed at a mass ratio of 10:1 for 10 minutes to replace the bismuth-containing humic acid complex. The remaining steps and parameters are the same as those in the preparation of the ternary composite expanding agent in Example 4.
[0107] Comparative Example 4
[0108] In this comparative example, the similarities with Example 4 will not be repeated, and the differences are as follows:
[0109] In the first step of preparing the ternary composite expanding agent, 3-chloro-2-hydroxypropyltrimethylammonium chloride is not used; instead, unmodified sodium lignin sulfonate is used directly. The amount of sodium lignin sulfonate is the same as that of quaternized sodium lignin sulfonate in Example 4. The remaining steps and parameters are the same as those in the preparation of the ternary composite expanding agent in Example 4.
[0110] Comparative Example 5
[0111] In this comparative example, the similarities with Example 4 will not be repeated, and the differences are as follows:
[0112] The conductive particles were replaced with an equal mass of commercially available activated carbon, the conductive framework was replaced with an equal mass of commercially available acetylene black, and the ternary composite expansion agent was replaced with an equal mass of barium sulfate, sodium lignin sulfonate, and humic acid mixed mechanically for 10 minutes. The remaining composite material preparation steps and parameters were the same as in Example 4.
[0113] Performance Test Results and Analysis
[0114] The negative electrode composite materials for energy storage lead-carbon batteries prepared in Examples 1-4 and Comparative Examples 1-5 were coated onto negative electrode grids. The negative electrode grids were made of lead-calcium alloy, with a grid thickness of 2.5 mm and rib cross-sectional dimensions of 1.0 mm × 1.8 mm. The amount of paste applied was approximately 150 g / plate. After curing and drying, the negative electrode plates were obtained. The positive electrode plates were made of lead-calcium alloy grids, with a grid thickness of 2.8 mm and rib cross-sectional dimensions of 1.2 mm × 2.0 mm. After coating with positive electrode lead paste, the grids were cured and dried. The positive electrode active material was PbO2, and the amount of paste applied was approximately 180 g / plate. The separator was made of AGM ultrafine glass fiber separator, with a thickness of 2.0 mm, a porosity of 92%, an acid absorption of 8.5 g / g, and a resistivity of approximately 0.003 Ω·cm. The negative electrode plate, separator, and positive electrode plate were assembled into a 2V / 100Ah single-cell battery in the order of negative electrode-separator-positive electrode-separator-negative electrode. Dilute sulfuric acid with a density of 1.28 g / cm³ was injected, with an electrolyte volume of approximately 600 mL per cell. The formation process was as follows: constant current charging at 0.1C for 16 hours at 25°C, followed by a 2-hour resting period, then discharge at 0.1C to a termination voltage of 1.8V, followed by a 2-hour resting period, and finally constant current charging at 0.2C for 8 hours to complete the formation.
[0115] Initial capacity testing was conducted at 25℃, with charging at 0.2C for 8 hours, resting for 1 hour, and then discharging at 0.2C to the termination voltage of 1.8V. The discharge capacity was recorded. HRPSoC cycle life testing was conducted at 25℃, with constant current charging at 0.3C to a single-cell voltage of 2.45V, resting for 10 minutes, followed by discharging at 0.3C for 30 minutes and resting for 10 minutes. This process constituted one cycle, and the number of cycles until the discharge capacity decayed to 80% of the initial capacity was recorded. Hydrogen evolution overpotential testing employed a three-electrode system, with the negative electrode as the working electrode, the Hg / Hg2SO4 electrode as the reference electrode, and a platinum sheet as the counter electrode. The electrolyte was dilute sulfuric acid with a density of 1.28 g / cm3. The test temperature was 25℃, and linear sweep voltammetry was performed with a scan range of -1.0V to -1.5V and a scan rate of 1 mV / s. The onset potential of the hydrogen evolution reaction was recorded; a more negative potential indicated a higher hydrogen evolution overpotential and a lower tendency for hydrogen evolution. The degree of sulfation was tested after the battery was disassembled following HRPSoC cycling. The negative electrode plate was washed with deionized water, vacuum dried at 60°C for 12 hours, and then subjected to X-ray diffraction analysis. The full width at half maximum (FWHM) of the characteristic diffraction peak of lead sulfate at approximately 25.8° 2θ was measured. A larger FWHM indicates finer lead sulfate grains and a lower degree of sulfation. For the electrode bonding strength test, the cured and dried negative electrode plate was used, and the peel strength between the active material and the grid was measured according to the electrode bonding strength test method in GB / T19638.2. The test results are shown in Table 1.
[0116] Table 1 Analysis of Test Results
[0117] sample Initial capacity / Ah Cycle life / times Hydrogen evolution initiation potential / V Lead sulfate peak width at half maximum (°) Peel strength / N Example 1 102.5 1850 -1.38 0.42 18.5 Example 2 101.8 1780 -1.35 0.4 17.8 Example 3 103.2 1920 -1.4 0.45 19.2 Example 4 104.5 2100 -1.42 0.48 20.5 Comparative Example 1 100.5 1200 -1.25 0.35 16.5 Comparative Example 2 99.8 950 -1.28 0.38 12 Comparative Example 3 101.2 1350 -1.3 0.36 17 Comparative Example 4 101.5 1400 -1.32 0.37 17.2 Comparative Example 5 98.5 800 -1.22 0.32 14.5
[0118] As shown in Table 1, Example 4 had the highest cycle life of 2100 cycles, followed by Example 3 at 1920 cycles, Example 1 at 1850 cycles, and Example 2 at 1780 cycles. The cycle life of all four examples was significantly higher than that of all comparative examples. Example 2 had the lowest cycle life among the four examples, but it was still higher than the 1400 cycles of Comparative Example 4. In Example 4, all parameters were at their optimal values: the polydopamine coating thickness was moderate, the bismuth anchor quantity was sufficient, and the pyrolysis temperature of 290℃ balanced the conductivity of the carbon layer and the thermal stability of the lead core. The bismuth nanoparticles in the nitrogen-doped carbon layer were uniformly distributed, resulting in a significant hydrogen evolution suppression effect. The CVD temperature of 700℃, time of 30 min, and acetylene flow rate of 80 mL / min in the conductive framework ensured sufficient filling of the conductive carbon black within the channels without clogging the micropores. After liquid-phase reduction deposition, the lead surface layer was uniform and dense, exhibiting good interfacial bonding with the lead paste. The components in the ternary composite expander are in a well-proportioned ratio, and ball milling for 70 minutes ensures uniform dispersion. The quaternized sodium lignin sulfonate, the bismuth-containing humic acid complex, and the barium sulfate complement each other, continuously suppressing hydrogen evolution and sulfation during charge and discharge. Therefore, the battery in Example 4 can withstand more cycles under HRPSoC conditions with slow capacity decay.
[0119] As can be seen from the hydrogen evolution onset potential data in Table 1, Example 4 has the most negative hydrogen evolution onset potential, reaching -1.42V, followed by Example 3 at -1.40V, Example 1 at -1.38V, and Example 2 at -1.35V. The hydrogen evolution onset potentials of all four examples are significantly negative compared to all comparative examples, indicating that the synergistic effect of bismuth nanoparticles and nitrogen-doped carbon in the conductive particles of this application does indeed improve the hydrogen evolution overpotential. Compared to Example 1, Comparative Example 1 did not contain bismuth pentahydrate in its conductive particles; after the pyrolysis of polydopamine, only a nitrogen-doped carbon layer was formed, without bismuth nanoparticle anchoring. Although nitrogen doping can change the electronic structure of the carbon surface through the lone pair electrons of nitrogen atoms, thereby increasing the hydrogen evolution overpotential, the effect is far less than that of bismuth-nitrogen synergy. Therefore, the hydrogen evolution onset potential is only -1.25V, a positive shift of 130mV compared to Example 1, indicating a significantly enhanced tendency for hydrogen evolution. Comparative Example 5 used commercially available activated carbon instead of conductive particles. The surface of activated carbon is rich in oxygen-containing functional groups, resulting in a low hydrogen evolution overpotential and a hydrogen evolution initiation potential of only -1.22V. During the cycling process, the electrolyte lost water severely, and the cycle life was only 800 cycles.
[0120] Compared to Example 1, Comparative Example 2 omitted liquid-phase reduction deposition in the conductive framework, and no metallic lead layer was present on the porous ceramic surface. Although carbon black within the pores provided some conductivity, the ceramic surface was chemically inert and had poor wettability with the lead paste. After formation, interfacial voids appeared around the ceramic, leading to localized breakage of the conductive network, uneven current distribution, and exacerbated localized overcharge and discharge. Therefore, the hydrogen evolution initiation potential was -1.28V, and the cycle life was only 950 cycles. Compared to Example 1, Comparative Example 3 used a simple mechanical mixture of humic acid and bismuth oxide in the ternary composite expander instead of a bismuth-containing humic acid complex. The bismuth oxide particles were unevenly dispersed in the lead paste, resulting in coarse particles and uneven distribution of the reduced metallic bismuth, leading to poor hydrogen evolution inhibition. Therefore, the hydrogen evolution initiation potential was -1.30V, and the cycle life was 1350 cycles. Compared with Example 1, Comparative Example 4 used unmodified sodium lignin sulfonate, which mainly relies on van der Waals forces for adsorption on the lead surface. It is easily desorbed during cycling. After passivation of the lead surface, the effective electrochemical area decreases, the local current density increases, and hydrogen evolution is aggravated. Therefore, the hydrogen evolution initiation potential is -1.32V.
[0121] The trend of the lead sulfate half-peak width (HWHM) is consistent with the cycle life and hydrogen evolution overpotential. The HWHM of Example 4 is 0.48°, Example 3 is 0.45°, Example 1 is 0.42°, and Example 2 is 0.40°. A larger HWHM indicates finer lead sulfate grains and a lighter degree of sulfation. Comparative Example 5 has the smallest HWHM, indicating that the commercially available expanding agent is a simple mixture of barium sulfate, sodium lignin sulfonate, and humic acid, with uneven dispersion. The heterogeneous nucleation effect of barium sulfate is not fully utilized, resulting in coarse lead sulfate crystals. The HWHM of Comparative Example 1 is 0.35°, lower than Comparative Examples 3 and 4. This is because there is no bismuth anchoring in the conductive particles, but the nitrogen-doped carbon layer still exists, which has a certain inhibitory effect on lead sulfate crystal growth. The synergistic effect of the quaternized sodium lignin sulfonate and the bismuth-containing humic acid complex in the ternary composite expanding agent makes the sulfation inhibition effect better than that of Comparative Example 5.
[0122] As can be seen from the peel strength data in Table 1, Example 4 has the highest peel strength at 20.5 N, followed by Example 3 at 19.2 N, Example 1 at 18.5 N, and Example 2 at 17.8 N. Comparative Example 2 has the lowest peel strength at 12.0 N. This is because the porous ceramic surface lacks a metallic lead layer, resulting in a lack of chemical bonding between the ceramic and the lead paste. After formation, the interfacial voids gradually expand during cycling, exacerbating the shedding of active material. Comparative Example 5 has a peel strength of 14.5 N. Commercially available acetylene black lacks ceramic skeleton support, resulting in poor dispersion and easy detachment in the electrode plate, leading to a loose electrode plate structure. The peel strengths of Comparative Examples 1, 3, and 4 are 16.5 N, 17.0 N, and 17.2 N, respectively, all lower than that of Example 1. This is because the modification effects of conductive particles and the ternary composite expander also indirectly affect the electrode plate bonding strength. The bismuth-anchored carbon layer and the quaternized sodium lignin sulfonate improve the dispersibility and plasticity of the lead paste, making the electrode plate structure more dense and uniform.
[0123] Test results show that Examples 1-4 of this application are superior to Comparative Examples 1-5 in terms of cycle life, hydrogen evolution suppression, sulfation suppression, and electrode bonding strength. This indicates that the structural design and functional coordination of conductive particles, conductive framework, and ternary composite expander can indeed solve the problems of carbon material segregation, ceramic interface voids, and the separation of hydrogen evolution and sulfation functions in existing lead-carbon battery anode composite materials, thereby improving the cycle performance of energy storage lead-carbon batteries under HRPSoC conditions.
[0124] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A composite material for the negative electrode of a lead-carbon battery for energy storage, characterized in that, By weight, the composite material comprises 100 parts lead powder, 2-3.5 parts conductive particles, 1.5-2.5 parts conductive skeleton, 1.8-2.5 parts ternary composite expansion agent, 0.1-0.15 parts short fiber, 9-11 parts dilute sulfuric acid, and 11-13 parts pure water. The conductive particles are obtained by reacting lead powder in an alkaline buffer solution containing dopamine hydrochloride and bismuth nitrate pentahydrate to obtain lead powder coated with a precursor, and then pyrolyzing and grinding the lead powder coated with the precursor. The conductive framework is obtained by chemical vapor deposition of porous alumina ceramic to form a porous ceramic-conductive carbon black intermediate. The porous ceramic-conductive carbon black intermediate is then immersed in an aqueous solution of lead acetate, and hydrazine hydrate solution is added dropwise for liquid-phase reduction deposition. The mixture is then filtered and vacuum dried to obtain the final product. The ternary composite expanding agent is prepared by ball milling barium sulfate, sodium quaternized lignin sulfonate, and a bismuth-containing humic acid complex. The sodium quaternized lignin sulfonate is prepared by reacting sodium lignin sulfonate with 3-chloro-2-hydroxypropyltrimethylammonium chloride, followed by filtration, washing, vacuum drying, and grinding. The bismuth-containing humic acid complex is prepared by mixing bismuth pentahydrate with humic acid, aging, filtering, washing, and vacuum drying.
2. The energy storage lead-carbon battery negative electrode composite material according to claim 1, characterized in that, The method for preparing the conductive particles includes the following steps: dispersing lead powder in Tris-HCl buffer solution with a pH of 8.0-8.5, adding dopamine hydrochloride and bismuth nitrate pentahydrate, stirring openly at room temperature for 18-24 hours, filtering, washing with water, and vacuum drying at 60-80℃ to obtain lead powder coated with precursor. Lead powder coated with precursor is pyrolyzed in a tube furnace, and after natural cooling, the product is ground for 10-15 minutes and passed through a 200-mesh sieve to obtain conductive particles.
3. The energy storage lead-carbon battery negative electrode composite material according to claim 2, characterized in that, The mass ratio of lead powder, dopamine hydrochloride, and bismuth nitrate pentahydrate is 100:3-5:0.8-1.
5.
4. The energy storage lead-carbon battery negative electrode composite material according to claim 2, characterized in that, The specific steps and parameters of the pyrolysis are as follows: the lead powder coated with the precursor is placed in a tube furnace and heated to 280-300℃ at a rate of 2-3℃ / min under a nitrogen atmosphere, and held at that temperature for 2-3 hours.
5. The energy storage lead-carbon battery negative electrode composite material according to claim 1, characterized in that, The method for preparing the conductive framework includes the following steps: placing spherical porous alumina ceramics with a particle size of 20 μm in a chemical vapor deposition furnace, using acetylene as the carbon source and nitrogen as the carrier gas, and performing chemical vapor deposition at 680-720℃ for 25-35 min to obtain a porous ceramic-conductive carbon black intermediate. The porous ceramic-conductive carbon black intermediate was then immersed in an aqueous lead acetate solution and ultrasonically dispersed for 25-35 minutes. After that, hydrazine hydrate solution was added dropwise, and the mixture was stirred at room temperature for 2.5-3.5 hours to carry out liquid-phase reduction deposition. The mixture was then filtered and vacuum dried at 80-100℃ to obtain the conductive framework.
6. The energy storage lead-carbon battery negative electrode composite material according to claim 5, characterized in that, The concentration of the lead acetate aqueous solution is 0.08-0.12 mol / L, the mass percentage concentration of the hydrazine hydrate solution is 12%-18%, the amount of lead acetate aqueous solution used is 20-40 mL per gram of porous ceramic-conductive carbon black intermediate, the amount of hydrazine hydrate solution used is 50-100 mL per liter of lead acetate aqueous solution; the flow rate of the acetylene is 50-100 mL / min, and the flow rate of the nitrogen gas is 200-400 mL / min.
7. The energy storage lead-carbon battery negative electrode composite material according to claim 1, characterized in that, The preparation method of the ternary composite expanding agent includes the following steps: Step 1: Preparation of sodium quaternized lignin sulfonate: Dissolve sodium lignin sulfonate in water to prepare a 15%-25% (w / w) solution. Adjust the pH to 9-10 with sodium hydroxide. Add 3-chloro-2-hydroxypropyltrimethylammonium chloride and react at 60-70℃ for 3-4 hours. Cool the reaction solution to room temperature and adjust the pH to 2-3 with dilute hydrochloric acid. After standing for 2-3 hours, filter the solution. Wash twice with dilute hydrochloric acid solution at pH 2-3, then wash once with deionized water, and finally wash twice with ethanol. Dry under vacuum at 60-70℃ to constant weight. Grind the solution and pass it through a 100-200 mesh sieve to obtain solid sodium quaternized lignin sulfonate. Step 2: Preparation of bismuth-containing humic acid complex: Dissolve bismuth nitrate pentahydrate in 0.5-1 mol / L dilute nitric acid to prepare a bismuth nitrate pentahydrate solution with a concentration of 0.05-0.1 mol / L; dissolve humic acid in water to prepare a solution with a mass fraction of 8%-12%, and adjust the pH to 3-4 with dilute nitric acid to obtain a humic acid solution; add the humic acid solution to the bismuth nitrate pentahydrate solution dropwise over 0.5-1 h, maintaining a stirring speed of 200-300 r / min during the addition process, stirring at room temperature for 2-3 h, aging for 12 h, filtering, washing the filter cake with deionized water until the washing liquid is neutral, and vacuum drying at 60-70℃ to obtain the bismuth-containing humic acid complex; The third step is to prepare a ternary composite expanding agent: barium sulfate, sodium quaternized lignin sulfonate, and bismuth-containing humic acid complex are ball-milled at a mass ratio of 5-6:1.5-2:1 to obtain the ternary composite expanding agent.
8. The energy storage lead-carbon battery negative electrode composite material according to claim 7, characterized in that, The mass ratio of humic acid to bismuth nitrate pentahydrate is 11-19:1; the mass ratio of sodium lignosulfonate to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:0.3-0.
5. The specific parameters for ball milling are as follows: barium sulfate, sodium quaternized lignin sulfonate, and bismuth-containing humic acid complex are placed in a ball mill, zirconium oxide balls are used as the grinding medium, the ball-to-material mass ratio is 6:1-8:1, the rotation speed is 300-350 r / min, and the ball milling time is 60-80 min.
9. The energy storage lead-carbon battery negative electrode composite material according to claim 1, characterized in that, The short fibers are polyester short fibers with a length of 2-4 mm and a diameter of 10-20 μm; the mass fraction of the dilute sulfuric acid is 40%.
10. A method for preparing a negative electrode composite material for an energy storage lead-carbon battery as described in any one of claims 1-9, characterized in that, The method includes the following steps: dry mixing lead powder, conductive particles, conductive skeleton, ternary composite expander, and short fibers for 6-8 minutes; adding pure water and wet mixing for 4-5 minutes; adding dilute sulfuric acid while stirring for 10-12 minutes; continuing stirring for 16-20 minutes while maintaining a stirring speed of 150-250 r / min; and controlling the mixing temperature to not exceed 52℃ to obtain the negative electrode composite material for energy storage lead-carbon batteries.
Citation Information
Patent Citations
Long-life lead-acid storage battery electrode plates and making method thereof
CN106099119A
Lignin inorganic oxide composite binder, preparation thereof and application of lignin inorganic oxide composite binder in hard carbon negative electrode
CN120843057A